Phenomenological study of nursing experiences in Iran and Sweden - Nikbakht Nasrabadi A; Parsa Yekta Z; Emami A (Tehran University of Medical Sciences, 2004)
Introduction: Phenomenological investigation of nursing profession and nurses' perspectives in Iran in comparison to a caring-oriented nursing system (Sweden) is the main purpose of this study. Materials and Methods: Interpretive phenomenology was used to conduct this study. Data gathering methods included observation and semi-structured interviews with 1) Iranian nurses, 2) Swedish nurses, 3) Iranian nurses who graduated from nursing in Iran but work as nurse in Sweden and 4) Iranian nurses who work as nurse in Sweden and studied nursing there. Content Analysis was used for data analysis. Results: Except humanitarian approach to nursing in a small group of Iranian nurses, the difficulties experienced due to work conditions and environmental factors have lead them to a state of burnout. Although caring is a primacy in nursing, enough attention is not being paid to it in nursing education programs. Conclusion: Burnout as a main theme which emerged in this study affects all aspects of nursing profession in Iran. The nature of nursing profession, its routine tasks and poor public image as well as sociocultural factors have influenced nursing negatively.